Analysis of Cost and Quality Comparison of Recycling Project Fence (RFP) with Zincalume Project Fence : Case Study Project X in Jakarta - Egar Albert; Yopi Lutfiansyah (Journal of World Conference (JWC), 2021)
The fence of the project is a fence established on the project land for the safety boundary of the project during the period of implementation of the project, according to The Perda Dki No.7 Year 1991 the fence of the project should pay attention to the safety and harmony of the surroundings and have a height of at least 2.5 meters. The cost of installing a project fence requires a relatively high cost on a project that has a long perimeter area. Project Fence usually uses zincalume material and is often a problem of construction waste because the material is not durable, this led to the innovation of Recycling Project Fence (RFP). In this study, the authors conducted a cost and quality comparison between the two materials by conducting cost analysis in accordance with the contractor's cost analysis and disseminating 2 stages of questionnaires on quality comparison to experts and respondents who are contractor employees who are accustomed to using RFP. The results of the questionnaire will be conducted to test validity and reliability using statistical software and analysis of relative importance index (RII). The result of this study is the total cost required for PPDU Rp.1,097,864,515 and the total cost required for fencing the zincalume project Rp. 980,546,545 where PPDU is more expensive Rp. 117,317,979 or 10.69%. with the most influential variables on the comparison of RFP quality with Zincalume are Features (0.860), Durability (0.851), Aesthetics (0.850), Performance (0.823), Reliability (0.693). So that the cost of fencing zincalume project is more effective while ppdu quality is more effective to use.